Kualitas dan Kuantitas Forward Looking Disclosure Berdasarkan Prediksi Kebangkrutan Perusahaan - Vitalia Thesa Pramaishella; Ari Budi Kristanto (Jurnal Bingkai Ekonomi (JBE), 2019)
This study attempts to see if there were differences in the quality of the forward looking disclosure predicted the company was bankrupty and not predicted bankrupt companies. It is also to know whether there were differences in quality the disclosure of forward looking disclosure between companies that predicted went bankrupt and companies that do not predicted bankrupt in listed company in the Indonesia Stock Exchange in 2017 financial report. The result showed that there are differences quantity forward looking disclosure between companies that do not predicted bankrupt. Next the result of the second study not indicating the defference of quality forward looking disclosire between the company which is predicted bankrupt and companies that predicted not bankrupt.